A characterization of the oval cone in PG(3, q). (3rd April 2021) - Zuanni, Fulvio
Abstract: We prove that in PG (3, q ), a ( q 2 + q + 1) -set K of type ( m, m + q, m + 2 q )2 such that any external line is contained in exactly one m -secant plane is an oval cone. Hence, if q is odd, then K is a quadratic cone.